Analisis Gaya Bahasa dalam Novel Hujan Karya Tere Liye : Kajian Stilistika - Nuril Isabillah; Ahmad Ilzamul Hikam (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the figurative language in the novel Hujan by Tere Liye using a stylistic approach and to evaluate its relevance as teaching material for Indonesian language education. The main focus is on comparative figurative language such as personification, metaphor, simile, and hyperbole found in the novel. The research method applied is qualitative descriptive, with data collection through reading, noting, and classifying stylistic elements. The results show that these figurative languages play an important role in enriching the aesthetic value of the work, developing character portrayal, creating atmosphere, and effectively delivering moral messages. Moreover, the use of these stylistic features can help students improve their literary appreciation and language skills more deeply. Therefore, the novel Hujan is suitable as instructional material to enhance students’ interest and understanding of literary works